Pengaruh Gaya Belajar Terhadap Motivasi Belajar Peserta Didik Pada Mata Pelajaran Ipa Kelas Viii Uptd Smp Negeri 10 Parepare - Sudirman, Mutiara Khaerunnisa (Edukimbiosis: Jurnal Pendidikan IPA, 2025)
This study aims to examine the learning styles of eighth-grade students in the science subject at UPTD SMP Negeri 10 Parepare, determine the level of their learning motivation, and analyze whether students’ learning styles have a significant influence on their learning motivation in the science subject. This research uses a quantitative approach with an associative research design. The population consists of 163 students at UPTD SMP Negeri 10 Parepare, with a sample of 62 students selected using the Slovin formula. The data analysis techniques used in this study include descriptive analysis, normality test, linearity test, correlation coefficient test, and hypothesis testing using partial and simultaneous tests. The results show that the dominant learning style among eighth-grade students in the science subject at UPTD SMP Negeri 10 Parepare is the visual style, with a percentage of 84.7%. The level of students’ learning motivation for the science subject is 80%, and there is a significant influence of learning style on learning motivation, amounting to 39.7%.